2009
DOI: 10.1210/jc.2008-2836
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Reproductive Features before and during Puberty in Daughters of Women with Polycystic Ovary Syndrome

Abstract: Hyperinsulinemia and an increased ovarian volume are present in PCOSd before the onset of puberty and persist during pubertal development. The biochemical abnormalities of PCOS appear during late puberty. Considering the early onset and the nature of the alterations, PCOSd constitute a high-risk group for metabolic and reproductive derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(151 citation statements)
references
References 41 publications
8
135
0
8
Order By: Relevance
“…this regard, we did not find any signs of virilization in this cohort of female newborns. However, we cannot exclude that abnormal enzymatic activities in placentas from PCOS women can lead to subtle effects on ovarian or metabolic function, as daughters of women with PCOS show an altered follicular mass and insulin resistance at early age [22,23]. Supporting this concept, animal models of prenatal androgen exposure have demonstrated that female fetuses develop a PCOS phenotype in adulthood [24].…”
Section: Commentsmentioning
confidence: 99%
“…this regard, we did not find any signs of virilization in this cohort of female newborns. However, we cannot exclude that abnormal enzymatic activities in placentas from PCOS women can lead to subtle effects on ovarian or metabolic function, as daughters of women with PCOS show an altered follicular mass and insulin resistance at early age [22,23]. Supporting this concept, animal models of prenatal androgen exposure have demonstrated that female fetuses develop a PCOS phenotype in adulthood [24].…”
Section: Commentsmentioning
confidence: 99%
“…Intra-and inter-assay coefficients of variation were, respectively, 9.6% and 8.6% for T, 5.6% and 9.8% for A, and 3.5% and 8.5% for 17-OHP. The testosterone RIA assay was validated against liquid chromatography plus tandem mass spectrometry as previously described (29).…”
Section: Assaysmentioning
confidence: 99%
“…Additionally, the reproductive capacity of adolescents also undergoes non-pathological changes during pubertal development that are influenced by the secretion of gonadotropins. These changes are expressed by irregular menstrual patterns and PCOM on ultrasonography, and may even persist for 2 years after menarche [2,15,16,17]. Because all three sets of criteria include abnormal ovulatory patterns and PCOM, the diagnosis in adolescence remains challenging.…”
Section: Pcos In Adolescentsmentioning
confidence: 99%
“…Among obese adolescents, IR is commonly detected and appears similarly in relation to adolescent PCOS [3,17]. Likewise, insulin-lowering treatment in PCOS with metformin has a positive effect on peripheral insulin sensitivity, PCOM, androgen levels, and obesity [35].…”
Section: Biological Originmentioning
confidence: 99%